THE CURRENT GLOBAL CRISIS: CAUSES AND SOLUTIONS - Sabina G. ŢUCA (SEA: Practical Application of Science, 2013)

(untitled)
In recent years the global economy has been facing a very severe economic and financial crisis. The leading economies of the world are going through a period of deep recession. The aim of this article is to emphasize the causes of the current crisis as well as the measures taken to counteract its effects. In order to achieve this purpose, representative articles on the subject have been analyzed. Compared to other crises, the current crisis is based on totally different causes. That is why the countries affected by the crisis should take unusual measures for the recovery of their economy. However, whatever measures had been already taken, the economic crisis is not over, predictions in this regard being mostly pessimistic.